2019
DOI: 10.1108/ilt-01-2018-0016
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on sealing performance of VL seals based on mixed lubrication theory

Abstract: Purpose This paper aims to research the influence of pressure, friction factors, roughness and actuating speed to the mixed lubrication models of outstroke and instroke. Design/methodology/approach Mixed lubrication model is solved by finite volume method, which consists of coupled fluid mechanics, deformation mechanics and contact mechanics analyses. The influence of friction factor on the finite element model is also considered. Then, contact pressure, film thickness, friction and leakage have been studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…LAT is used by Siddiqui et al [23] for finding the effect of magnetohydrodynamics on Newtonian calendaring. Most recently Xu et al [24] used LAT to analyze the sealing performance of VL seals.…”
Section: Introductionmentioning
confidence: 99%
“…LAT is used by Siddiqui et al [23] for finding the effect of magnetohydrodynamics on Newtonian calendaring. Most recently Xu et al [24] used LAT to analyze the sealing performance of VL seals.…”
Section: Introductionmentioning
confidence: 99%
“…By putting Equation (19) into (23), it is shown that one must choose the value of k , k and k which will converge the sliding surface value to the zero. When the sliding surface value approaches zero then it will show the sliding surface phase rather than reaching phase.…”
Section: Sliding Mode Controlmentioning
confidence: 99%
“…The performance of the opposed pad hydrostatic bearing is improved by using a membrane-type hydrostatic restrictor [17]. The H loop and inner loop methods are used for stabilizing the shaft and reducing vibrations [18,19]. Integration of tribo-mechatronics and control has divided the active hydrostatic bearings into three classes.…”
Section: Introductionmentioning
confidence: 99%
“…The solid contact mechanism between two surfaces that are sliding relative to each other is quite complex and is not yet sufficiently known. 28 As the Greenwood-Williamson model is widely used in current studies of reciprocating seals, 7,[9][10][11][13][14][15][16][17][18][19][20] this contact model is also employed in this paper. A Gaussian distribution is assumed to exist for these asperities, and the solid contact pressure can be calculated by the Greenwood-Williamson contact model 29 :…”
Section: Contact Mechanismmentioning
confidence: 99%
“…The coupling method has been widely employed in the study of single seals such as O-rings, [4][5][6][7][8][9] U-cup seals [10][11][12][13][14] and some combined seals such as Step seals 15,16 and VL seals. [17][18][19][20] However, the above studies focused mainly on the sealing performance under normal temperature conditions, while little research has been conducted on the sealing performance in a wide temperature range. Nikas et al 21 have carried out pioneering and detailed experimental work on the rectangular ring 20 and proposed a fast calculation method for reciprocating seals at temperatures of −54°C, 23°C and 135°C, respectively.…”
Section: Introductionmentioning
confidence: 99%